Comparative Study of Mortgage Auctions in Indonesia and Singapore - Maskanah, Ummi; Bahyudin, Mukhamad; Buana, Tubagus Langlang; Zulkarnain, Muhammad Azka Izzaturrahman (Golden Ratio of Law and Social Policy Review, 2026)
Auction practices in Indonesia have been known since 1908 through the Vendu Reglement and have evolved from conventional to digital mechanisms. Singapore also has a tradition of auctions dating back to the British colonial period in the 19th century. This study aims to compare mortgage foreclosure auction practices in Indonesia (a civil law tradition) and property foreclosure in Singapore (a common law tradition), focusing on efficiency, transparency, and legal certainty. The method used is normative legal research with a regulatory and comparative approach, grounded in a literature review. The results of the study show that Indonesia has a strong legal basis through PMK No. 213/PMK.06/2020, which provides formal legal certainty, including through Auction Reports as authentic deeds. However, the effectiveness of auction digitisation via lelang.go.id remains constrained by inter-agency integration. In addition, there is the potential for third-party objections to auction results (derdenverzet, i.e., resistance or objections from third parties), which can hinder the finality of auction results. In contrast, Singapore implements an integrated digital auction system supported by strict regulations, including the Auctioneers' Licences Act. Legal certainty is strengthened by the finality of transactions under the fall of the hammer principle, which enables rapid contract binding. Overall, Singapore's auction system demonstrates higher efficiency and accountability and can serve as a reference for Indonesia in strengthening end-to-end integration and consistency in the implementation of national auctions.